British nurses' attitudes to electroconvulsive therapy, 1945–2000. (4th June 2015) - Adams, John
Abstract Aim The aim of the study was to collect and analyse historical material on nurses' attitudes to electroconvulsive therapy in Britain between 1945–2000. Background Electroconvulsive therapy became widely used in Britain from the late 1940s onwards and remains in current use, but became one of the main targets of the 'antipsychiatry' movement of the 1960s and 1970s. Design A cultural history design was used to recreate the perspectives of mental health nurses in the period under review. Method A range of primary sources including journal articles, textbooks and oral history sources were combined to create a coherent historical account. Findings The controversy surrounding electroconvulsive therapy created a deep‐seated ambivalence towards it among mental health nurses. While a sizeable minority were critical of its use and may have taken steps to avoid involvement with it, most acquiesced in providing the treatment. Recorded incidents of outright refusal to participate are few. Conclusion Mental health nurses' views on electroconvulsive therapy are reflective of the profession's growing knowledge of the use of evidence in debating whether particular therapies should be used.